Diagnóstico da hanseníase paucibacilar: resposta imune celular a proteínas recombinantes do Mycobacterium leprae - Sampaio, Lucas Henrique Ferreira (2008)
Objetives: To test T cell effector/memory immune response to M leprae recombinant proteins assessed by IFN-y production among leprosy patients and controls. Methods: The following study groups were assessed: A. Paucibacilary leprosy (PB; n=13); B. Multibacilary leprosy (MB; n=10), PB and MB were newly diagnosed untreated patients; C. Pulmonary tuberculosis, HIV negative (TB; n=10); D. Healthy endemic controls (EC; n=10); E. Multibacilary household contacts (HHC; n=13). The following M.leprae recombinant proteins were tested: ML0091; ML0276; ML0398; ML0541; ML0543; ML0840; ML0953; ML1011; ML1213; ML1623; ML2044 and the fusion proteins ML46f and ML56f at 10ug/ml using Whole Blood Assay (WBA), 450mL/well, 37oC, 5%CO2. After 24 hours incubation, plasma was collected to quantitate IFN-y by ELISA (QuantiFERON CMI, Cellestis, Australia). Results- Based on IFN-y levels, M. leprae recombinant proteins were classified into: A - “Immunogenic and Specific”: ML0276, ML1623, ML0091, ML46f, ML0840, ML2044; B - “Immunogenic and not specific”: ML0398; C -“Not Immunogenic”: ML1011, ML57f, ML0541, ML0316, ML0543, ML1213, ML0953. Conclusions- Plasma IFN-y levels among PB leprosy and healthy household contacts indicated six potential candidates for the diagnosis of PB leprosy represented by the following immunogenic and specific M. leprae recombinant proteins: ML0276, ML1623, ML0091, ML46f, ML0840 and ML2044.